Obesity and diabetes in menopause: prevention and therapeutic approach - Godziejewska-Zawada, Małgorzata (Menopause Review/Przegląd Menopauzalny, 2013)
The incidence of obesity and diabetes as well as metabolic syndrome gradually increases with age. In our consciousness, in women, menopause is directly related with a higher incidence of these abnormalities. Up to now there has been no evidence that menopause is the reason. Some studies documented that menopausal women had a higher amount of abdominal fat. This and abrupt decrease of estrogen levels appear to be the main reasons for a sudden rise in the incidence of cardio-vascular diseases in postmenopausal women. In most studies, behavioral intervention (i.e. diet with caloric restriction and physical activity) is the most effective prevention of obesity and diabetes. In early menopause, hormonal therapy may prevent the increase of central adiposity. In women in early menopause with central adiposity or BMI ≥ 35 kg/m2 metformin may be helpful in diabetes prevention. In older age, behavioral therapy is the most effective. Hormonal therapy and metformin therapy may harmful rather than helpful. Polish and American Diabetes Associations recommended fast walking as a best method of exercise. In some studies, Tai Chi could be useful to prevent osteoporosis by strengthening the muscle of lower extremities as well as the sense of equilibrium. Below we present essential problems of obesity and diabetes in menopause as well as methods of their prevention.